Social networks moderate the association between physical fitness and cognitive function among community-dwelling older adults: a population based study - Foong, Hui Foh; Ibrahim, Rahimah; Hamid, Tengku Aizan; Haron, Sharifah Azizah (BioMed Central, 2021)
Background: Physical fitness declines with age. Low levels of physical fitness appear to be a risk factor of cognitive impairment. Literature elucidates social networking as a potential moderator for the relationship between physical fitness and cognitive impairment. Present study aimed to examine the relationship between physical fitness and cognitive function among community-dwelling older Malaysians, and if social network moderates said relationship. Methods: Data of 2322 representative community-dwelling older adults were obtained from the first wave of the “Longitudinal Study on Neuroprotective Model for Healthy Longevity” national survey. Cognitive function, physical fitness and social network was assessed through Malay-version of Mini-Mental State Examination, 2-min step test and Lubben Social Network Scale-6 respectively. Moderated hierarchical multiple regression was employed to investigate if social networks moderate the relationship between physical fitness and cognitive function. Results: A positive association between physical fitness and cognitive function were found upon controlling for covariates. Moderated hierarchical multiple regression revealed social networks to be a moderator of the association between physical fitness and cognitive function. When physical fitness was low, those with small social network revealed lowest cognitive function. Conclusions: Social networks moderated the relationship between physical fitness and cognitive function as older adults with low levels of physical fitness and small social networks revealed lowest cognitive function. Therefore, community support or peer-based interventions among physically unfit older adults should be implemented to promote cognitive function.